Chronic Renal Failure and Bleeding Due to Dieulafoy Lesion: Two Case Reports and Literature Review - Gustavo Adolfo Hernández Valdez; Diana Estefanía Ibarra García; Juan Antonio Contreras Escamilla; Janette Alejandra Gamiño Gutierrez; Francisco Manuel Tonatiuh Carrillo Beltran; Ulises Solis Gomez; Jocelyn Nataly Quintero Meléndez; Ivan Alejandro Medina Jimenez; Marco Antonio González Villar; Jorge Rojas Morales (Medicine and Medical Research: New Perspectives Vol. 4, 2024)
Dieulafoy’s lesions are rare vascular malformations of the gastrointestinal tract. Dieulafoy’s lesion was first reported by Gallard in 1884 and then described in detail by Georges Dieulafoy in 1898. A Dieulafoy’s lesion is an aberrant vessel that does not reduce in caliber when it extends from the submucosa to the mucosa. Damage to this artery can cause severe and intermittent arterial bleeding from small vascular stumps that are difficult to visualize. Multiple factors have been proposed that increase the risk of upper gastrointestinal bleeding in end-stage renal disease patients including platelet dysfunction due to uremia, high prevalence of arteriovenous malformations, various co-morbidities like cardiovascular disease, diabetes mellitus, liver cirrhosis and old age. Furthermore, these catastrophic bleeding episodes frequently result in hemodynamic instability and the need for transfusion of multiple blood products. Recently, uremic syndrome has been identified as a risk factor for gastric mucosal lesions. We present two clinical cases of acute digestive bleeding due to the Dielafoy lesion with chronic kidney disease as the main cause, where two different therapies were performed endoscopically. Endoscopic therapy is still the first-line diagnostic and/or treatment option for Dieulafoy’s lesion. This study concluded with the results of the patients that the best therapy was the application of the hemostatic hemoclip on the injury vs. the injection with adrenaline on the wound site. Uremia is identified as a risk factor for upper gastrointestinal bleeding in patients with pre-existing Dieulafoy lesions, as well as a higher incidence of new bleeding.